Causes influencing the length of stay of cardiac surgery patients in the intensive care unit - Dimitropoulou, Nikoleta; Stamou, Aggeliki; Marvaki, Christina (Health & Research Journal, 2015)
Introduction: The incidence of postoperative morbidity has increased, a fact which may lead to prolonged hospitalization of the patient in the Intensive Care Unit (ICU) and generally in the hospital. Aim: The aim of the present study was to explore the complications after cardiac surgery responsible for the prolonged stay of patients in the ICU. Material and method: The studied sample consisted of 80 patients who were hospitalized in the Intensive Care Unit General Hospital of Athens from January 2013 to June 2014. For data collection a special registration form with information coming from the medical records of patients was used. Data analysis was performed by the IBM SPSS 21.0 (Statistical Package for Social Sciences). Results: Regarding to demographic characteristics Regarding the demographic characteristics and medical history of the studied sample, the majority were male (58.7%, n=47), with a mean age of 73 years and an average hospital stay of 3.3 days. The major causes of prolonged ICU stay was respiratory failure (20%, n=16), arrhythmias (17.5%, n = 14), bleeding (15%, n=12), myocardial infarction (11.3%, n=9), and pulmonary edema (10%,n=8). Τhe bivariate analysis showed statistical relationship to the level of 0,20 (p<0,20) between the prolonged ICU stay and age, coronary artery disease as the cause of entry, coronary artery bypass, diabetes melitus and chronic obstructive pulmonary disease. Conclusion: Patients with a history of heart failure, diabetes or obstructive pulmonary disease seems to have a greater chance for a prolonged ICU stay after cardiac surgery. Early recognition of demographic and clinical factors that may lead to the prolonged ICU stay can provide very important information about how to improve perioperative care of the patient.